EPHX1 and GSTP1 polymorphisms are associated with COPD risk: a systematic review and meta-analysis - Qinjun Yang; Qinjun Yang; Qinjun Yang; Wanqiu Huang; Dandan Yin; Lu Zhang; Yating Gao; Jiabing Tong; Jiabing Tong; Jiabing Tong; Zegeng Li; Zegeng Li; et al. (Frontiers in Genetics, 2023)
Background: Chronic obstructive pulmonary disease (COPD) affects approximately 400 million people worldwide and is associated with high mortality and morbidity. The effect of EPHX1 and GSTP1 gene polymorphisms on COPD risk has not been fully characterized.Objective: To investigate the association of EPHX1 and GSTP1 gene polymorphisms with COPD risk.Methods: A systematic search was conducted on 9 databases to identify studies published in English and Chinese. The analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses reporting guidelines (PRISMA). The pooled OR and 95% CI were calculated to evaluate the association of EPHX1 and GSTP1 gene polymorphisms with COPD risk. The I2 test, Q test, Egger’s test, and Begg’s test were conducted to determine the level of heterogeneity and publication bias of the included studies.Results: In total, 857 articles were retrieved, among which 59 met the inclusion criteria. The EPHX1 rs1051740 polymorphism (homozygote, heterozygote, dominant, recessives, and allele model) was significantly associated with high risk of COPD risk. Subgroup analysis revealed that the EPHX1 rs1051740 polymorphism was significantly associated with COPD risk among Asians (homozygote, heterozygote, dominant, and allele model) and Caucasians (homozygote, dominant, recessives, and allele model). The EPHX1 rs2234922 polymorphism (heterozygote, dominant, and allele model) was significantly associated with a low risk of COPD. Subgroup analysis showed that the EPHX1 rs2234922 polymorphism (heterozygote, dominant, and allele model) was significantly associated with COPD risk among Asians. The GSTP1 rs1695 polymorphism (homozygote and recessives model) was significantly associated with COPD risk. Subgroup analysis showed that the GSTP1 rs1695 polymorphism (homozygote and recessives model) was significantly associated with COPD risk among Caucasians. The GSTP1 rs1138272 polymorphism (heterozygote and dominant model) was significantly associated with COPD risk. Subgroup analysis suggested that the GSTP1 rs1138272 polymorphism (heterozygote, dominant, and allele model) was significantly associated with COPD risk among Caucasians.Conclusion: The C allele in EPHX1 rs1051740 among Asians and the CC genotype among Caucasians may be risk factors for COPD. However, the GA genotype in EPHX1 rs2234922 may be a protective factor against COPD in Asians. The GG genotype in GSTP1 rs1695 and the TC genotype in GSTP1 rs1138272 may be risk factors for COPD, especially among Caucasians.